Environment Friendly Open Pit Mining Systems and Reclamation Post-Mining Efforts to Improve the Quality of Land Resources and Soil Biodiversity - GITOSUWONDO, SUBOWO (Indonesian Center for Agriculture Land Resource Development, 2011)
Conventional open pit mining systems can changing the landscape and soil surface ecosystem balance, reducing soil productivity and environmental quality. On the other hand the good mining activities can increase national income, reduce pollution, decrease land slope, improve the thickness of topsoil, decrease soil density, increase infiltration- percolation and reduce soil erosion. Good implementation control of the open pit mining with the preservation of land resources and soil biodiversity can be achieved by: (1) mining blocks done from the bottom area, (2) reclamation carried out directly after the completion of mining, (3) formation of land surface with a wide terrace bench >5 m, vertical-interval bench terraces <2 m, the percentage of slope Â± 60%, (4) removing the top layer of soil (topsoil) was placed back on the top layer with a thickness >20 cm and enriched with lime, organic matter, fertilizer or biofertilizer (5) biorehabilitation with endogeic earthworms and planting of legume cover crops as pioneer plants to accelerate the natural succession, and (6) maintenance up to a climax ecosystem as expected